Reconstructing the Values of Islamic Religious Education based on Melayu Islam Beraja in Brunei Darussalam - Arvaddin Hamasy Al Qosam; Mohammad Ahmed Mahee bin Haji Samry; Mahmud Arif; Dwi Ratnasari (Universitas Sebelas Maret, 2024)
The country of Brunei Darussalam is a country with a geographical area that is not large, but has many unique features, apart from the people living in abundance, this country is a country that adheres to the Malay Islam Beraja ideology, which is an ideology. which combines Malay culture, Islamic teachings and the Royal system. This research tries to examine and dig deeper into the role of MIB and its relationship to Islamic education. The purpose of writing this article is to find out what the Islamic education system is like in Brunei Darussalam and the role of MIB and its application to Islamic education in Brunei Darussalam. This type of research is field research using a qualitative approach. Meanwhile, data collection techniques use observation, interview and documentation techniques. The data analysis technique for this research uses three analysis techniques, namely data reduction, data presentation, and data conclusion. This research examines the validity of the data using data triangulation techniques, namely source triangulation, technical triangulation and time triangulation. The research process lasted for 1 month. The results of this research are that in general the concept of education in Brunei Darussalam is similar to countries in the world in general such as Malaysia and Singapore. However, what is unique about education in Brunei is that there are 3 main subjects taught in schools, namely bilingual subjects, Islamic Melayu Beraja and increased resources including vocational and vocational studies